Development of Sharing Task and Jumping Task in Direct Proportion using Lesson Study and PBL - Elisa Mayang Sari; Ratu Ilma Indra Putri (Universitas Ahmad Dahlan, 2019)
This Research’s purpose is producing questions/case study in direct proportion topic focused on Map and Model, and analyse students’ answer in solving these arranged questions through lesson study for learning community (LSLC) and PMRI approach using problem based learning (PBL) method. Research subject are students of grade VII of Junior High School 1 Palembang. From this research, it results a LKPD questions about direct proportion in Map and Model that consist of three cases, such as determine new scale from known scale in problem solving (C2), determine size of Limas House miniature from known scale and sizes in problem solving (C3), and check for errors from a given comparison in problem solving (C4). Based on the results of the analysis of Students answer small group, the average score obtained by students in problem 1 (sharing task) is 73.5, problem 2 (sharing task) average student score is 55, and average student score in problem 3 (jumping task) is 48.5. So these three problems are well-billed and can be used to the next stage of the field test.